Fabrication of edible special wettability coating on polystyrene substrate and application in yogurt storage. (February 2023) - Hou, Jumin; Liu, Shuqiu; Su, Mengqi; Fan, Yuyan; Liu, Yan; Yan, Xiaoxia
Abstract: The yogurt adherence always caused enormous waste of food sources due to sticking onto the package inner walls. So, carnauba wax, silica, and carboxymethylcellulose (CMC) were mixed together as an emulsion to be sprayed, and fabricated an edible special wettability coating on the polystyrene substrate for reducing the yogurt residual rate. The contact angle, slide angle and yogurt residual rate on the coating were respectively (141.32 ± 3.48) °, (7.51 ± 1.65) ° and (3.77 ± 1.99) %, revealing a good application in yogurt package. The coating was fabricated compactly and robustly through element mapping, functional groups recognition, and crystalline analysis. The coating could also tolerate the acid circumstance at a wide pH range with little yogurt residual. Afterwards, the emulsion was sprayed onto the inner wall of commercial cups to fabricate the coating for yogurt storage. It could be observed that the yogurt residual rate was (7.40 ± 0.36) % in coated cups, which was significantly less than the control cups (9.64 ± 0.83) % ( p  < 0.05) after 21 days storage. Besides, the coating had no negative effects on the yogurt qualities, and none of the coating ingredients released into the yogurt during storage. It could be found that there was no significant relationship between the viscosity and the residual rate ( p  > 0.05) due to the coating, but the viscosity and the contact angle on the coating had a positive correlation ( R  = 0.701, p  < 0.01). Thus, an edible special wettability coating was fabricated for solving the adherence problems generally existing in the yogurt industry. Highlights: The bonding mechanisms between substrate and coating were revealed. The effects of the coating on yogurt quality during storage shown insignificant. Yogurt viscosity determined the contact angle but not the residual rate on the coating.